Types of classifications in law - Viachorka, Vitali Y. (Journal of the Belarusian State University. Law, 2023)
In this article the author describes approaches to structuring the whole variety of applied classifications in the legal environment. In addressing the issue of the types of classifications in law, the author proposes to establish the logic for constructing classification criteria and to form a structural model of criteria for classifying objects of the legal environment on the basis of the built-in logic. The paper presents examples of the most common classifications at various levels of its detection in law, as well as recommendations that should be followed when deciding on the criteria (features) of classification. The conclusion about the significance of classification for legal doctrine is made. This significance which consists in facilitating the «transition» from the stage of empirical accumulation of knowledge to the level of theoretical synthesis, that is, the classification enhances the axiological significance of scientific material. Classification, according to the author, creates opportunities to search for more advanced methods and forms of ordering the legal space, serves to create a more perfect system and is focused on achieving the best result in this area of activity. Dealing with a properly built classification, processes and phenomena in the legal sphere are more deeply comprehended, inconsistencies, contradictions, problems of legal regulation are revealed much more successfully and with less effort and time, and measures are taken to eliminate them.
Keywords: classification; classification in law; legal classification; criterion (sign) of classification in law